Bush bedtime - Broekstra, Lorette (Allen & Unwin Crows Nest, NSW, 2018)
A super cute, colourful story exploring early language concepts, featuring baby Australian animals. There were ten out of bed in the middle of the night. But one by one the bush babies begin to get sleepy ..